Dribbling speed predicts goal-scoring success in a soccer training game - Wilson, R. S.; Smith, N. M. A.; Melo de Souza, N.; Arruda Moura, F. (Scandinavian Journal of Medicine & Science in Sports, 2020)
The aim of this study was to explore the underlying bases of goal-scoring ability of junior soccer players. Male players (mean age 17.2 years, SD = 1.3) were recruited from an elite Brazilian football academy. We assessed each individual's dribbling and sprinting speed along five 30 m paths varying in curvature from 0 to 1.37 radians/m. We also quantified each player's ability to dribble the ball through a series of 15 cones using six different techniques. Dribbling, sprinting, and technical dribbling were then compared with an individual's goal-scoring ability as assessed when competing against one defender and a goalkeeper protecting a full-sized goal (N = 20-48 attempts/ individual). Goal-scoring success was significantly positively associated with their sprint speed (r = .60; P = .014), dribbling speed (r = .81; P < .0001), and technical dribbling (r = .49; P = .022). An individual's percentage of shots saved was only significantly associated with their dribbling speed (r = -.81; P < .001), with faster dribblers less likely to have their shots saved. Based on the full multivariate model for goal-scoring success (adjusted r2 = .60; P < .001), dribbling speed was the only significant correlate (t = 3.51; P < .001). Our study demonstrates that our metric of dribbling speed, as measured along curved paths, was associated with goal-scoring success. Future studies should focus on specific training regimes aimed at improving dribbling ability, and measuring any impact on the creation of goal-scoring opportunities and number of goals scored.